Maximum power point tracking for PV systems under partial shading conditions using current sweeping. (15th March 2015) - Tsang, K.M.; Chan, W.L.
Graphical abstract: Highlights: A novel approach for tracking the maximum power point of photovoltaic systems. Able to handle both the uniform insolation and partial shading conditions. Maximum power point tracking based on current sweeping. Abstract: Partial shading on photovoltaic (PV) arrays causes multiple peaks on the output power–voltage characteristic curve and local searching technique such as perturb and observe (P&O) method could easily fail in searching for the global maximum. Moreover, existing global searching techniques are still not very satisfactory in terms of speed and implementation complexity. In this paper, a fast global maximum power point (MPPT) tracking method which is using current sweeping for photovoltaic arrays under partial shading conditions is proposed. Unlike conventional approach, the proposed method is current based rather than voltage based. The initial maximum power point will be derived based on a current sweeping test and the maximum power point can be enhanced by a finer local search. The speed of the global search is mainly governed by the apparent time constant of the PV array and the generation of a fast current sweeping test. The fast current sweeping test can easily be realized by a DC/DC boost converter with a very fast current control loop. Experimental results are included to demonstrate the effectiveness of the proposed global searching scheme.